CRTAP mutation in a patient with Cole‐Carpenter syndrome. (21st January 2015) - Balasubramanian, Meena; Pollitt, Rebecca C.; Chandler, Kate E.; Mughal, M. Z.; Parker, Michael J.; Dalton, Ann; Arundel, Paul; Offiah, Amaka C.; Bishop, Nicholas J.
<x xml:space="preserve">Abstract</x> In 1987, Cole and Carpenter reported two unrelated infants with multiple fractures and deformities of bone, with a skeletal phenotype similar to severe osteogenesis imperfecta. In addition, these patients also had proptosis, blue sclerae, hydrocephalus, and a distinct facial gestalt. They were reported to be of normal intelligence. Radiologically, these patients had characteristic skeletal manifestations including craniosynostosis and deformities similar to severe progressive osteogenesis imperfecta. Since the first description, there have only been a few other reports of patients with a similar phenotype. Collagen studies performed in reported patients have been normal. The molecular basis of this syndrome has not been elucidated and the inheritance pattern is still unknown. We report on a child with Cole‐Carpenter syndrome phenotype who has a homozygous c.118G>T mutation in exon 1 of the CRTAP gene. We describe the clinical features and correlate this with her molecular results. This is the first report towards elucidating the molecular basis of Cole‐Carpenter syndrome. © 2015 Wiley Periodicals, Inc.